Aktivitas Antioksidan Serbuk Biji Salak (Salaca Zalacca Gaertn. Voss) Menggunakan Metode Dpph (1,1 Diphenyl-2- Picrylhydrazil) - Rejeki, Desi; Pramiastuti , Oktariani; Candra Wiguna, Julio (PT. Pubsains Nur Cendekia, 2024)
Salak seeds are a part of the snake fruit plant that is often ignored by the public and considered as waste. Based on several research results, snake fruit has good nutritional content for health, snake fruit contains iron, is high in carbohydrates, calcium, phosphorus and vitamin C. This research aims to determine the antioxidant content in snake fruit powder. The DPPH method was chosen because it is one of the methods for determining antioxidant activity that is the fastest, simplest, and has been widely used with various solvents such as methanol and ethanol. The solvent used in this research was methanol pro analysis, because it has very high purity properties. The activity test results used the DPPH method and the IC50 value obtained for salak seed powder was 90.89 ppm, this result is classified as a strong antioxidant.